Pengaruh Media Tanam terhadap Laju Pertumbuhan Bibit Kopi (Coffea sp) - Kadha, Faustinus; Saba Agu, Yakobus Pffeferius Edvent; Neonbeni, Eduardus Yosef; Kaauni, Gabriel Ludgerus (Fakultas Pertanian, Sains, dan Kesehatan, Universitas Timor, 2023)
Coffee is a superior commodity that has a high selling value. Good coffee seedlings can produce high quality coffee. The use of planting media in coffee seedling is expected to have a positive impact on coffee growth. This research used a completely randomized design (CRD) with a single factor pattern consisting of 4 treatments, each treatment repeated 3 times. The media used are soil as control media (T0) = (100%), soil and sand (T1) in a ratio of (1:1), soil, sand, compost (T2) in a ratio of (1:1:1), soil, biocar compost sand (T3) in the ratio (1:1:1). here were 4 treatment combinations and were repeated 3 times so that there were 12 experimental units. The results of the research showed that (i) The treatment of soil: sand: biochar compost had a significant effect on the growth of coffee plants. This can be seen from the real influence on the parameters of number of leaves and stem diameter. (ii) Soil planting media treatment: sand: biochar compost is the best planting media treatment in increasing the growth of coffee plants. This can be seen from the highest values in the parameters of plant height, number of leaves, and stem diameter. The treatment of soil: sand: biochar compost had a significant effect on the growth of the number of leaves and stem diameter.